Academic library as a cultural and educational center - D. M. Khafizov; S. G. Smolina (Библиосфера, 2017)
Enlightenment as well as cultural and educational activity plays a key role in forming cultural values. But educational activity of academic library is perceived in a limited context, that is why the article objective is to analyze an academic library activity as an educational and cultural center. The activity is expressed by a set of educational-information, leisure and cultural events as instruments to promote and develop scientific knowledge, to stimulate users’ reading activity, to form general human culture and specific competences. The article describes different approaches of understanding the educational activities, the emphasis is made on cultural and educational activities of university libraries, federal state educational standards of higher education and higher vocational training in various fields are analyzed to reveal the essence of the libraries activity. In the process of comparative analysis of cultural-educational activities authors studied sites and public reports of Russian university libraries (a case of South Ural State University Scientific Library) and world libraries (library complexes of Oxford University, Munich Technical University, Harvard University, University of Oslo). As a result, main forms of cultural-educational activities were identified and systematized taking into consideration advantages and problems of implementation.